1986
DOI: 10.1128/jb.165.2.412-419.1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of nitrogenase-derepressed mutant strains of cyanobacterium Anabaena variabilis

Abstract: A positive selection method for isolation of nitrogenase-derepressed mutant strains of a filamentous cyanobacterium, Anabaena variabilis, is described. Mutant strains that are resistant to a glutamate analog, L-methionine-D,L-sulfoximine, were screened for their ability to produce and excrete NH4' into medium.Mutant strains capable of producing nitrogenase in the presence of NH4' were selected from a population of NH4+-excreting mutants. One of the mutant strains (SA-1) studied in detail was found to be a cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…169,1987 on May 12, 2018 by guest http://jb.asm.org/ Downloaded from nitrogenase activity in the presence of DCMU (Table 4), it failed to stimulate growth ( Table 1). The observed enhancement of nitrogenase activity by either pyruvate or glucose is in agreement with reports on the utilization of organic compounds to support nitrogenase activity in other nitrogenfixing cyanobacteria, including heterocystous species capable of photoheterotrophic growth (15,20,24). Cyclic photophosphorylation obviously supplies the ATP needed, an interpretation supported by the high nitrogenase activity of the samples containing DCMU.…”
Section: Hydrogenase (N2)supporting
confidence: 79%
See 2 more Smart Citations
“…169,1987 on May 12, 2018 by guest http://jb.asm.org/ Downloaded from nitrogenase activity in the presence of DCMU (Table 4), it failed to stimulate growth ( Table 1). The observed enhancement of nitrogenase activity by either pyruvate or glucose is in agreement with reports on the utilization of organic compounds to support nitrogenase activity in other nitrogenfixing cyanobacteria, including heterocystous species capable of photoheterotrophic growth (15,20,24). Cyclic photophosphorylation obviously supplies the ATP needed, an interpretation supported by the high nitrogenase activity of the samples containing DCMU.…”
Section: Hydrogenase (N2)supporting
confidence: 79%
“…The ammonia concentration was monitored with Nessler reagent (20 (16,22), this isolate, designated strain SF1, was identified as a Synechococcus sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An MSXresistant mutant strain of A. variabilis that requires glutamine, but only when grown on N2, NO3, or low concentrations of ammonia, has recently been reported (26). It has been shown that glutamine is taken up by filaments of A. variabilis but growth of the cells on glutamine as the sole nitrogen source occurred only at high concentrations of the amino acid; this growth, which occurred under an Ar-02-CO2 atmosphere, was attributed to ammonia produced from glutamine (5).…”
mentioning
confidence: 99%
“…For example, lack of N promotes N fixation by diazotrophic cyanobacteria, but this is more associated with the lack of ammonia than other N sources [96]. As such, N fixation occurs in the presence of nitrate [85,97,98]. Despite the association with eutrophic environments, on a temporal scale, cyanoHABs generally occur during periods when the standing stock of N and P are at their lowest [78,99].…”
Section: Characteristics Of Bloom Forming Cyanobacteriamentioning
confidence: 99%